Two for the road - Butcher, Nancy (New York : HarperEntertainment, 2001)
While in Florida on their school trip, Mary-Kate searches for her lost diary and Ashley worries about competition from Dana Woletsky.
"A Parachute Press book."
Keywords: Twins; Sisters